ISLAM DI AFRIKA UTARA BAGIAN BARAT AL-MURABITHUN DAN AL-MUWAHHIDUN - Syahraeni, Andi (RIHLAH, 2013)
The rise and fall of Umayyad caliphate occurred in the early of the eleventh century. During this period, the caliphate was governed by the minister council. Due to the absence of the control from the central government, many small kingdoms, governed by the Mulk clans, proclaimed their independence in the regions such as Sevilla, Cordova, and Toledo. Some of them were the Murabithun and the Muwahhidun dynasty. Yusuf bin Tasyin (1061-1106 M) was the king who was successful in developing the Murabithun dynasty. He expanded his territory to include some regions. This indicates that the Murabithun was the first barbarian tribe who colonized most of the areas in the west part of North Africa. The Muwahhidun dynasty was initially a religious movement but later known as a name of a Kingdom in Maghreb, North Africa. The weakening of the control and discipline of the local authorities was the reason for the fall of the great al-Mahdi Ibn Tumart.